2018
DOI: 10.1038/s41379-018-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Alternative PDGFD rearrangements in dermatofibrosarcomas protuberans without PDGFB fusions

Abstract: Dermatofibrosarcoma protuberans is underlined by recurrent collagen type I alpha 1 chain-platelet-derived growth factor B chain (COL1A1-PDGFB) fusions but ~ 4% of typical dermatofibrosarcoma protuberans remain negative for this translocation in routine molecular screening. We investigated a series of 21 cases not associated with the pathognomonic COL1A1-PDGFB fusion on routine fluorescence in situ hybridization (FISH) testing. All cases displayed morphological and clinical features consistent with the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
75
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 45 publications
4
75
0
3
Order By: Relevance
“…Also, it should be noted that a very small percentage of DFSPs do not appear to exhibit the classic COL1A1‐PDGFB fusion. Recently, it has been discovered that over half of these DFSPs instead harbor rearrangements of PDGFD , and another 40% have cryptogenic COL1A1‐PDGFB fusions . While it is possible that our case represents a DFSP with a novel translocation, the increasing evidence is that this is not the case.…”
Section: Discussionmentioning
confidence: 80%
“…Also, it should be noted that a very small percentage of DFSPs do not appear to exhibit the classic COL1A1‐PDGFB fusion. Recently, it has been discovered that over half of these DFSPs instead harbor rearrangements of PDGFD , and another 40% have cryptogenic COL1A1‐PDGFB fusions . While it is possible that our case represents a DFSP with a novel translocation, the increasing evidence is that this is not the case.…”
Section: Discussionmentioning
confidence: 80%
“…A special DFSP variant is associated with a COL6A3‐PDGFD fusion gene and typically occurs on the breast of females . There have also been some reports of DFSP patients with an EMILIN2‐PDGFD fusion gene . Knowledge about these molecular changes allows for targeted therapy of DFSP.…”
Section: Diagnosismentioning
confidence: 99%
“…The first agent to be approved for systemic treatment of DFSP is the multikinase inhibitor imatinib, showing objective response rates of about 50 % in clinical trials. mit einer EMILIN2-PDGFD-Genfusion beschrieben [8]…”
mentioning
confidence: 99%
“…The in‐frame fusion of the 5′ end of COL1A1 to the 3′ end of PDGFB is present in greater than 90% of DFSPs when a combination of FISH and reverse transcription polymerase chain reaction (RT‐PCR) techniques are employed . Two recent studies showed that in the approximately 4% of cases that are negative for this fusion in initial routine testing, RNA sequencing analysis has shown that 40% of cases do indeed have the classical COL1A1 ‐ PDGFB fusion, but another 55% of cases show a fusion between PDGFD and either COL6A3 or EMILIN2 . Cytogenetically, the COL1A1 ‐ PDGFB fusion is frequently in the form of a supernumerary ring chromosome; less often it is found as a linear translocation derivative .…”
Section: Discussionmentioning
confidence: 99%